MERDEKA SECARA FINANSIAL, MERDEKA DALAM MEMILIH: FINANSIAL SEBAGAI FAKTOR PENGAMBILAN KEPUTUSAN PERCERAIAN PADA WANITA - Arini Puspa Wardani; Mirna Nuralia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2024)
Divorce is currently a common occurrence in Indonesia. In 2022, 75.21% of divorce lawsuits were filed by a wife. There are various factors that cause divorce. But in the end, many women are still reluctant to divorce for fear of not being able to support their own lives and the stigma of widows attached to society. The author's goal is to find out the factors that cause divorce, then how a woman's financial ability affects the consideration of divorce, and society's labeling of a widow. In this study, the researcher used the literature review method. In this study the author found that the causes of divorce are quarrels, death of one of the parties, economy, domestic violence, and disharmony. A woman has many considerations for divorce even though she is financially capable because of the labeling of widows in society. However, financial factors are still one of the factors in divorce decision making. The difference between this research and previous research is that this research also discusses how finance affects divorce decision making in women.